Use of Mannose-Binding Lectin Gene Polymorphisms and the Serum MBL Level for the Early Detection of Neonatal Sepsis - Badawy, Magda; Mosallam, Dalia S.; Saber, Doaa; Madani, Hanan (Journal of Pediatric Genetics, 2018)
Background Mannose-binding lectin (MBL) is a component of innate immunity and is particularly important in neonates, in whom adaptive immunity has not yet completely developed. MBL deficiency and MBL2 gene polymorphisms are associated with an opsonization defect and have been associated with neonatal sepsis.Aim The aim of our study was to assess serum MBL levels and genotype MBL2 genes to determine whether they can serve as markers for predicting neonatal sepsis in neonatal intensive care units.Patients and Methods A case-control study was conducted with 114 neonates classified into two groups: the septic group included 64 neonates (41 preterm and 23 full-term infants), and the non-septic control group included 50 neonates (29 preterm and 21 full-term infants). Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was used to genotype MBL2 gene exon 1 (rs1800450) and (rs1800451) SNPs. Enzyme-linked immunosorbent assay (ELISA) was used to measure MBL serum concentrations.Results The polymorphic genotypes BB and AC at codons 54 and 57, respectively, showed higher frequencies than the wild-type genotype (AA) (14.1% versus 12.9% and 28.1% versus 19.4% respectively) in both groups, and this difference was greater in the septic group than in the non-septic group; however, the differences did not reach statistical significance. The B and C allele frequencies were also higher in the septic group than in the non-septic group, but the differences did not reach statistical significance (p = 0.282 and 0.394, respectively). The serum levels of MBL were significantly lower in the septic group than in the non-septic group (p = 0.028).Conclusion This study found no association between MBL levels or MBL2 exon 1 genotypes or alleles and neonatal sepsis risk. Further studies with larger sample sizes are needed to determine the role of the MBL2 gene as a risk factor and early predictor of neonatal sepsis.
Keywords: mannose-binding lectin; neonatal sepsis; gene polymorphism